Analyses of the suspended-load sedimentation process and its dynamics in reservoirs with high daily oscillations - Vrecl-Kojc, Helena (Acta geotechnica Slovenica, 2008)
The river water pumped into reservoirs with high daily oscillations, e.g. at pumping hydroelectric power plants, contains different amounts of suspended load depending on the time period and the riverćs discharge. This paper presents an analysis of the suspended-load sedimentation process that is based on the interaction between the sedimentation, i.e., the settling, velocity and the motion of the water. The settling velocity of spherical particles in the presence of a buoyancy force is a function of the particle size. Laboratory investigations of the suspended material from the river-watersamples have determined the ratio between the particle size and the concentration of suspended material with respect to the river discharge, the ratio between the concentration of suspended material in the water and the discharge, and the relationship between the concentration of suspended material and the discharge of water, which is for the first time expressed as an exponential function. The motion of the water in the reservoirs with high daily oscillations is solved by the three-dimensional modeling of the liquid streams. The evaluation of the results is presented for the case of the planned Kozjak pumping hydroelectric power plant on the River Drava.
Keywords: Drava; koncentracija; pretok; rečni sedimenti; sedimentacija; velikost delcev